2008
DOI: 10.1097/psy.0b013e31816b1aaa
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-Adrenal and Sympathetic Nervous System Responses to Stress in Women Remitted From Recurrent Major Depression

Abstract: In this group of women remitted from recurrent major depressive disorder, we found evidence of HPA system hypoactivity, both in the basal state and in response to a psychosocial stressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 35 publications
8
54
1
4
Order By: Relevance
“…This prolonged stress recovery seems to be specific to self-reported emotional responses and may be due to cognitive biases (De Raedt & Koster, 2010). Studies examining cortisol responses to stress in people in remission from depression found either no differences in cortisol reactivity/recovery from neverdepressed people (men in Bagley, Weaver, & Buchanan, 2011) or actually decreased cortisol responsivity relative to never-depressed people (women in Bagley et al, 2011;Ahrens et al, 2008). These findings suggest that interventions designed to improve stress recovery to increase resilience in remitted individuals may need to specifically target the vulnerable response modalities.…”
Section: Resilience In Remission 11mentioning
confidence: 96%
“…This prolonged stress recovery seems to be specific to self-reported emotional responses and may be due to cognitive biases (De Raedt & Koster, 2010). Studies examining cortisol responses to stress in people in remission from depression found either no differences in cortisol reactivity/recovery from neverdepressed people (men in Bagley, Weaver, & Buchanan, 2011) or actually decreased cortisol responsivity relative to never-depressed people (women in Bagley et al, 2011;Ahrens et al, 2008). These findings suggest that interventions designed to improve stress recovery to increase resilience in remitted individuals may need to specifically target the vulnerable response modalities.…”
Section: Resilience In Remission 11mentioning
confidence: 96%
“…Various studies reported increased sympathetic activity in depressed and anxious subjects compared with healthy controls, measured by different indices like spillover of norepinephrine (NE) and epinephrine (EPI), skin conductance responses, QT interval variability (QTvi), or the pre-ejection period (PEP) (Light et al, 1998;Esler et al, 1982;Guinjoan et al, 1995;Gold et al, 2005;Koschke et al, 2009;Barton et al, 2007). However, other studies reported no association between psychopathology and SNS activity or reported decreased SNS activity in subjects with depressive or anxiety disorders (Wilkinson et al, 1998;Esler et al, 2004;Roth et al, 2008;Ahrens et al, 2008), so findings remain inconclusive. A first major source of confounding in studies comparing SNS activity between depressed/anxious subjects and controls might be the different SNS indices used, with some measuring true NE release whereas others measure organ responsivity, which may also be influence by changes in clearance, re-uptake, or adrenoceptor sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os estudos, diversas foram as variáveis estudadas em deprimidos. Em 16 estudos tivemos variáveis em comum: em quatro, o paciente apresentava depressão na fase de remissão ou recuperação [18][19][20][21] ; em outros quatro, o que tornava os estudos parecidos era o fato de terem estudado o eixo em subtipos de depressão [22][23][24][25] ; em dois, estudou-se a interferência de eventos diários pelos quais passam as pessoas na atividade do eixo 21,26 ; em outros dois estudos, os autores optaram por avaliar o ritmo circadiano e/ou ultradiano do eixo 27,28 ; em mais dois estudos, verificou-se a resposta do eixo HPA em deprimidos, comparando com outra doença psiquiátrica [28][29][30] ; finalmente, em dois estudos, focou-se na interferência do sistema renina-angiotensina-aldosterona no eixo HPA 31 . As variáveis estudadas encontram-se como se segue na tabela 1.…”
Section: Métodosunclassified
“…Entre os artigos, o cortisol foi estudado em todos eles , seguido por ACTH 19,22,24,27,28,31,35,40 e prolactina 29,38 . O sulfato de dehidroepiandrosterona (DHEA-S) 32 e o CRH 36 só apareceram em um estudo cada.…”
Section: Métodosunclassified
See 1 more Smart Citation